Hollywood talks turkey the screen's greatest flops - McClelland, Doug
Hollywood Talks Turkey is for film-bluffs, star-gazers and anyone who has ever appreciated a film for being "so bad it's good." Here the stars, directors, producers and writers themselves comment on their biggest failures, from Clark Gable's 1930 disaster, Parnell, to Taylor and Burton's Cleopatra, to the more recent Heaven's Gate and Ishtar. Funny, candid, even apologetic, Hollywood Talks Turkey represents the industry's best remarks and reminiscences about its worst flops.